Γ‐Valerolactone: A Nontoxic Green Solvent for Highly Stable Printed Mesoporous Perovskite Solar Cells. Issue 7 (16th May 2021) - Worsley, Carys; Raptis, Dimitrios; Meroni, Simone; Doolin, Alexander; Garcia‐Rodriguez, Rodrigo; Davies, Matthew; Watson, Trystan
Abstract : Mesoscopic carbon‐based lead halide perovskite solar cells (CPSCs) represent a promising architecture for commercialization in the field of perovskite photovoltaics as they are stable, potentially low cost, and use easily scaled production methods. However, the use of toxic and psychoactive solvents such as dimethylformamide (DMF) and γ‐butyrolactone (GBL) currently limits their commercial viability: DMF introduces a significant health risk and GBL is subject to legal restrictions in many countries. The development of safe and effective solvent systems is therefore an essential step toward commercial viability. Herein, γ‐valerolactone (GVL) is presented as a nontoxic, biodegradable, green alternative to GBL for CPSC fabrication. Cells fabricated with a precursor concentration of 1.1 m and annealed at 45 °C exhibit comparable performance to standard GBL devices, achieving a champion power conversion efficiency (PCE) of 12.91% in a device of 1 cm 2 active area. Herein, it is proven that GVL is a viable alternative to GBL for CPSCs and enables research in countries where GBL is legally restricted and makes large‐scale CPSC manufacture more sustainable. Abstract : Carbon‐based lead halide perovskite solar cells are promising architectures for perovskite commercialization but rely on toxic or psychoactive precursor solvents, introducing health risks and legal restrictions. Herein, γ‐valerolactone (GVL) is presented as a γ‐butyrolactone (GBL) alternative. The optimized system achieves 12.91% PCE in a 1 cm 2 device, comparable with GBL, enabling continued research in countries where GBL is legally restricted.